English teaching through project based learning method, in rural area - Castañeda, Ruby Jackeline Pinzón (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The lack of motivation to learn English is a common problem in rural schools. Students do not perceive this language as a necessary tool for the future. This study aims at describing and interpreting to what extent the implementation of the Project-Based Method helps to increase English skills as well as the development of certain human values in students. This study also aims at discussing whether increasing language skills can be compared to learning and the improvement of relationships between students and teachers. Two mini-projects were developed with eighth grade students at a public institution of Boyacá, but for this paper we took into account only one of them. The results reveal three conclusions: first, students remain motivated to learn English when addressing issues related to their context, second, they hold in their mind the vocabulary when they associate it with pedagogical activities in which they are actively involved, and finally, the strategy of mini-projects strengthens the relationship between student and teacher even more.